2016
DOI: 10.1111/flan.12215
|View full text |Cite
|
Sign up to set email alerts
|

Language Learners’ Characteristics, Target Language Use, and Linguistic Development in a Domestic Immersion Context

Abstract: Second language acquisition research on the immersion context has focused primarily on study abroad, revealing the extent to which that context promotes learners’ developing linguistic and intercultural competence. However, little research has examined linguistic development in intensive, domestic immersion contexts. This study investigated the extent to which target language interactions in a seven‐week domestic immersion program predicted the acquisition of linguistic features that are not present in the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…However, when the researchers conceptualized this question by considering how the students chose to learn the language, results indicated that those who participated in extramural language activities (anything beyond the minimum required courses) placed an even higher value on improving pronunciation, based on the medium effect size (Table , p < 0.001; d = 0.70). Taken together, these results suggest that it may be important to explore a division between those students who participate in extramural activities and those who do not (e.g., Sundqvist & Sylvén, ), as other research has indicated a connection between extramural language activity and linguistic development (Isabelli‐García & Lacorte, ). The concept of extramural language study appears to be especially important for differentiating among lower‐level language learners.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, when the researchers conceptualized this question by considering how the students chose to learn the language, results indicated that those who participated in extramural language activities (anything beyond the minimum required courses) placed an even higher value on improving pronunciation, based on the medium effect size (Table , p < 0.001; d = 0.70). Taken together, these results suggest that it may be important to explore a division between those students who participate in extramural activities and those who do not (e.g., Sundqvist & Sylvén, ), as other research has indicated a connection between extramural language activity and linguistic development (Isabelli‐García & Lacorte, ). The concept of extramural language study appears to be especially important for differentiating among lower‐level language learners.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, making students aware of activities and opportunities beyond the classroom, sharing with them data on the relationship between the number of hours spent using the language and progress toward increased proficiency, inviting students to share with classmates the reasons and the ways in which they use the language outside the classroom, and obtaining an understanding of why students choose not to engage in extramural language activities may also be helpful. Language activity logs have been used in previous research in study abroad and at‐home‐immersion contexts (Freed, Dewey, & Segalowitz, ; Isabelli‐García & Lacorte, ; McManus, Mitchell, & Tracy‐Ventura, ; Sundqvist & Sylvén, ). Future research could adopt similar methods to explore the extramural language activity of learners enrolled in FL classes.…”
Section: Discussionmentioning
confidence: 99%
“…There are also domestic immersion programs, such as Middlebury Language Schools and Concordia Language Villages. While there are criticisms surrounding these programs-enforcing monolingualism using a language pledge, high tuition costs, limited cultural context-research does suggest their effectiveness in improving students' proficiency as well as their overall confidence in the target language (Isabelli-García & Lacorte, 2016;Segalowitz et al, 2004).…”
Section: Engaging With Communities and Languages Statesidementioning
confidence: 99%
“…Teachers could understand students’ responses to different teaching methods by observing their learning responses and understanding their performance in the class or learning process. Isabelli-García and Lacorte (2016) regarded learning outcome (LO) as the practice of various types of evaluation or tests on learners for a period of time after learning activity to understand their LO on the learned content. Lull and Bushman (2016) pointed out LO as an indicator to evaluate students’ absorption of course content; and, teachers’ teaching effectiveness could be judged based on students’ test performance.…”
Section: Literature Reviewmentioning
confidence: 99%